MINAT MEMBAYAR ZAKAT MASYARAKAT KAITANNYA DENGAN FAKTOR-FAKTOR DEMOGRAFI (Studi di Kecamatan Purbalingga) - Latif Nur Hakim; Dani Kusumastuti (JURNAL ILMIAH NUSANTARA, 2025)
This study is motivated by the low realization of zakat collection in Purbalingga Regency, despite its considerable potential. One of the identified causes is the low public interest in paying zakat. This research aims to examine the influence of demographic factors including income, gender, age, occupation, education level, and marital status on the community’s interest in paying zakat. The research method used is quantitative with a survey approach. The population in this study comprises residents of the Purbalingga Sub-District, with a sample of 100 respondents determined using the Slovin formula and a combination of cluster and accidental sampling techniques. Data were collected through questionnaires and analyzed using ordinal logistic regression with the help of SPSS software. The results show that the variables of income, age, and education have a significant influence on the interest in paying zakat. Meanwhile, gender, type of occupation, and marital status do not have a statistically significant effect. The results of this study imply the need to improve income, education, and public awareness as key factors influencing the intention to pay zakat. Zakat management institutions also need to optimize education and outreach programs in accordance with the community’s demographic characteristics.